The Portrait of Children Custody Rights in Indonesia: A Study of Mother's Rights in Child Custody from Gender Perspective - Mohamad Salman Podungge; Siah Khosyi'ah (Khazanah Sosial, 2022)
Divorce separates not only husband and wife but also parents and children. After the divorce, the role of the mother is identified as the best caregiver for the child. While the father's role is only limited to providing for the child's needs. The question is "whether a mother is the only one with custody rights of a child who has not been mumayiz or is not 12 years old yet? The study was carried out in a descriptive juridical method, with a gender approach, from two things: (1) the normative basis for determining child custody after divorce and (2) determining child custody for the father in a religious court. The findings of this study proved that caring for unmarried children is not the absolute right of a mother. Fathers also have the same rights, even more than a mother. The principle of "the best interest of the child" can be easily enforced by placing the custody rights of the father and mother equally.